Case on Integrated Time and Cost Monitoring of Construction Projects - M., Waris; Panda, Sitansu (Penerbit UMP, 2017)
The traditional approach of project time and cost performance measurement is generally based on direct monitoring in which there is a split-up between them. It does not truly relate the time versus cost performance of the project. Furthermore, this approach is not so much efficient to provide early warning indicators and forecast future performance trends. As a remedy of these limitations in traditional monitoring practices, this case has proposed Earned Value Analysis (EVA) which integrates the work scope, cost and time to enable effective project performance measurement.